Gustafson Gallery newsletter, fall '92 - Unidentified author (Colorado State University. Libraries, 1992)
Fall 1992 edition of Gustafson Gallery Newsletter. Contains items of interest and updates.
Keywords: Fashion -- History; Fashion -- Exhibitions